Pharmacological therapy for stable chronic obstructive pulmonary disease - Ruirui Duan; Baicun Li; Ting Yang (Chronic Diseases and Translational Medicine, 2023)
Abstract In recent years, emphasis has shifted from preventing and treating chronic obstructive pulmonary disease (COPD) to early prevention, early treatment, and disease stabilization, with the main goal of improving patients’ quality of life and reducing the frequency of acute exacerbations. This review summarizes pharmacological therapies for stable COPD.